Continuous emission versus freeze-out via Hanbury Brown–Twiss - Grassi, Frédérique; Hama, Yogiro; Padula, Sandra S. [UNESP]; Socolowski, Otavio (American Physical Society (APS), 2000)
The effect of the continuous emission hypothesis on the two-pion Bose-Einstein correlation function is discussed and compared with the corresponding results based on the usual freeze-out. Sizable differences in the correlation function appear in these different descriptions of the decoupling process. This means that, when extracting properties of the hot matter formed in high-energy heavy-ion collisions from the data, completely different conclusions may be reached according to the description of the particle emission process adopted. © 2000 The American Physical Society.